2015
DOI: 10.1016/j.msea.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

A nano lamella NbTi–NiTi composite with high strength

Abstract: A hypereutectic Nb 60 Ti 24 Ni 16 (at.%) alloy was prepared by vacuum induction melting, and a nano lamellae NbTi-NiTi composite was obtained by hot-forging and wire-drawing of the ingot. Microscopic analysis showed that NbTi and NiTi nano lamellae distributed alternatively in the composite, and aligned along the wire axial direction, with a high volume fraction (~70%) of NbTi nano lamellae. In situ synchrotron X-ray diffraction analysis revealed that stress induced martensitic transformation occurred upon loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Figure 2(a) shows the evolution of strain for the NWs and SMA matrix during the pretreatment. The strain of each component in our simulation is calculated according to the relationship between phase stress and lattice strain proposed by refs 21 , 22 , 23 , 25 and 28 . Figure 2(b) compares the cyclic tensile stress-strain curves of the SMA-NWs composite after the mechanical pre-treatment.…”
mentioning
confidence: 99%
“…Figure 2(a) shows the evolution of strain for the NWs and SMA matrix during the pretreatment. The strain of each component in our simulation is calculated according to the relationship between phase stress and lattice strain proposed by refs 21 , 22 , 23 , 25 and 28 . Figure 2(b) compares the cyclic tensile stress-strain curves of the SMA-NWs composite after the mechanical pre-treatment.…”
mentioning
confidence: 99%
“…in NiTi matrix sustains high elastic strain of 2.72% along with 2.53 GPa stress. 120 Al 1100 matrix embedded with NiTi particle exhibits better mechanical properties with no interfacial products. The shape memory characteristics of NiTi are utilized to induce residual tensile and compressive stresses in AL 1100 matrix.…”
Section: Niti Compositesmentioning
confidence: 99%
“…The second method is the introduction of strengthening phases into NiTi SMA matrix composites (SMACs). Soft/hard dual-phase composites have received a lot of attention recently because of their excellent mechanical properties and high damping capacities. For instance, it was reported that Ti 3 Sn showed excellent damping performance and desirable mechanical properties at a wide temperature range. Zhang et al observed that dense NiTi/Ti 3 Sn composites exhibited a high compressive strength of 3.0 GPa and a fracture strain of 33%. This excellent performance was attributed to lattice strain matching and the large interfacial area between the brittle Ti 3 Sn phase and the ductile NiTi phase in the composite.…”
Section: Introductionmentioning
confidence: 99%